The Implementation of Cognitive Strategy in Teaching English at SMPN 2 Sungguminasa - Ibrahim, Zahratul Aini Gani; Mahmud, Murni; Atmowardoyo, Haryanto (Har Press Indonesia, 2024)
This research aims to determine the implementation of cognitive strategy in teaching English and the influence of implementing cognitive strategy on students’ English learning process. Researchers conducted this research at SMPN 2 Sungguminasa. This research method is descriptive qualitative. The instruments in this research are observation, interviews and documentation. Data collection was carried out using observation sheets and interview techniques. Participants in this research were two English teachers at SMPN 2 Sungguminasa. The results of this research showed that English teachers implement this cognitive strategy by forming discussion groups, utilizing learning models (PJBL, PBL and direct methods) and conducting questions and answers to students. The influences of implementing this cognitive strategy are students who were initially very passive in learning English became motivated to participate in English learning after implementing this cognitive strategy. They spoke actively in expressing opinions, suggestions, creative ideas and actively collaborated. This shows that the results of the implementation of cognitive strategy have met the four indicators (critical thinking, creative thinking, decision making and problem solving). This strategy is very influential on students' learning process because it can improve students' thinking process through the application of cognitive strategies, so that students can develop their knowledge in learning.